Šiauliai County in the Correspondence of Povilas Višinskis - Jakaitė, Dalia (Acta humanitarica academiae Saulensis, 2019)
Sources of the article is the correspondence (reportages) written by literary, cultural, political activist Povilas Višinskis, that were published in the late 19th–early 20th centuries in “Varpas”, “Ūkininkas” and other publications. Višinskis enters into the history of writing as a publicist not only of large but also small texts by describing events, phenomena and problems related to a specific place and wider region. The aim of the article is to research the image of Šiauliai county through the prism of the relation between human and place, national and value identity, while looking at this region from the perspective of fundamental Višinskis’s provisions and style. Texts of Višinskis allow us to engage in a politically, socially, culturally rich and contradictory assessment of the events and phenomena of that time. Their connection with a specific place, allowing us to get to know this place and its wider context, emerges as a reliability criterion of ideological, cultural and social truth.The pursuit of truth in correspondence, manifesting through the criticism of the tsarist government, its laws or stereotypes entrenched in everyday life, takes the form of history, related to a specific place and its broader context. It allows a reader to get to know the rhythm of life of that place and at the same time the whole Lithuania, invites him to a more conscious relationship with his time in national, civic and other terms. A positive Višinskis’s view towards history and the present, the representation of social and cultural life is also very interesting. The connection of human and place is important in presenting culturally, politically and historically significant performances and gegužinės3. In the case of more militant or representative publicistic writing, the connection of human and place, supposing the identity of a local person, acts as a factor enhancing national identity and awareness.
Keywords: Povilas Višinskis; Šiauliai; place; publicistic writing; correspondence; locality; Lithuanian